2015
DOI: 10.3732/ajb.1500046
|View full text |Cite
|
Sign up to set email alerts
|

Responses of two understory herbs, Maianthemum canadense and Eurybia macrophylla, to experimental forest warming: Early emergence is the key to enhanced reproductive output

Abstract: Global warming might improve fitness of herbaceous species in deciduous forests, mainly by advancing their spring emergence. However, other impacts of global warming such as drier soils in the summer might partly reduce the carbon gain associated with early emergence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 69 publications
1
50
0
Order By: Relevance
“…First, trees and herbaceous spring wildflowers respond to warming at strikingly different rates. The possibility of contrasting tree and wildflower phenological responses to temperature have been suggested in earlier studies (Lapointe 2001;Neufeld & Young 2014;Jacques et al 2015;Augspurger & Salk 2017), but has not been demonstrated. Second, as a result of these differing phenological responsiveness between forest layers, the window of high light availability in the spring is decreasing with warmer spring temperatures.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…First, trees and herbaceous spring wildflowers respond to warming at strikingly different rates. The possibility of contrasting tree and wildflower phenological responses to temperature have been suggested in earlier studies (Lapointe 2001;Neufeld & Young 2014;Jacques et al 2015;Augspurger & Salk 2017), but has not been demonstrated. Second, as a result of these differing phenological responsiveness between forest layers, the window of high light availability in the spring is decreasing with warmer spring temperatures.…”
Section: Discussionmentioning
confidence: 96%
“…Our findings highlight unexpected consequences of phenological mismatch under climate change. Soil warming experiments have predicted fitness increases in forest herbs due to earlier spring emergence in warmed plots (Jacques et al 2015). Another study experimentally manipulated the emergence of spring ephemeral species, highlighting the physiological constraints of cold and shade on growth and reproduction for these species (Augspurger & Salk 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increases in air temperature resulting from climate change has been found to advance flowering times in understory herbs (e.g. Miller‐Rushing & Primack, ) and result in a generally longer growing season for most species (Cleland et al ., ), including forest herbs (Jacques et al ., ). Budbreak in overstory trees is determined primarily by photoperiod and air temperatures (Polgar & Primack, ), while aboveground emergence in understory herbs is determined by the timing of snowmelt and soil temperatures (Routhier & Lapointe, ).…”
Section: Discussionmentioning
confidence: 97%